Comparison of Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment intensive care unit scoring system as mortality predictors in intensive care unit patients with sepsis - Lokesh SB; Latha V (Asian Journal of Medical Sciences)
Background: Sepsis is a life-threatening organ dysfunction caused by a deregulated host response to infection. It is one of the leading causes of in-hospital mortality and morbidity among patients. It also results in significant morbidity and financial burden.